Measures of weed control by means of environmentally friendly technologies in summer-autumn period - O. Kurdiukova; O. Tyshchuk (Карантин і захист рослин)
Goal. To select criteria for optimal solutions for calculating techniques of effective control of weeds in the summer-autumn period, taking into account their biological groups, the level of weed infestation and harmfulness.